Curtains in CAD: Why Are They a Problem and How Do We Fix Them? - Nair, Akshar (Mathematical Software – ICMS 2020, 2020)
This paper is part of our ongoing research on the adaptation of Lazard’s CAD to benefit from equational constraints in formulae. In earlier work we combined the CAD methods of McCallum and Lazard so as to produce an efficient algorithm for decomposing a hypersurface rather than the whole of [Formula: see text] (exploiting an equational constraint [Formula: see text]). That method, however, fails if f is nullified (in McCallum’s terminology): we call the set where this happens a curtain. Here we provide a further modification which, at the cost of a trade off in terms of complexity, is valid for any hypersurface, including one containing curtains.